(untitled) (Journal of the Management Sciences, 2024)
It is truism that the legislature is generally seen as a crucial institution of the State in any democratic governance. This is attributable to the central role legislature plays in public policy process and the fact that its representative nature is such that strives to convey or put into cognizance the opinions of their constituents why performing their representative duties. In Anambra State, the Anambra State Legislature carries and indeed performs the duties of the legislature. This study therefore examines Legislature and Constituency Relations in Nigeria, with a specific emphasis on the Anambra State 6th House of Assembly. It argues that executive dominance of legislative activities, poor constituency project implementation and inadequate oversight function has grave legislative implications on the relationship of the constituents and the legislature in Anambra State. The study uses documentary methods which entails qualitative descriptive analysis. It is guided by structural functional theory. It concludes that imperious executive influences and poor relations of the legislators contributed to slow pace of development in the State within the period under study. It therefore recommends administrative and financial autonomy of the legislature both at Federal and State level to ensure effectiveness and unhindered legislative activities of the legislature in the State.